Estimating risk of acquiring SARS-COV2 infection in treatment-experienced PLWH: A case-control study - Pierluigi Francesco Salvo; Valentina Iannone; Francesca Lombardi; Arturo Ciccullo; Francesco Lamanna; Rosa Anna Passerotto; Gianmaria Baldin; Rebecca Jo Steiner; Andrea Carbone; Valentina Massaroni; Simona Di Giambenedetto; Alberto Borghetti (Global Epidemiology)
Background: Risk factors for acquiring SARS-CoV-2 infection in people living with HIV (PLWH) and the true relationship between HIV and SARS CoV-2, are still not fully understood. Objectives: The aim of this study was to identify the independent risk factors for SARS-CoV-2 acquisition in treatment experienced PLWH, shedding light on potential risk factors associated with SARS CoV-2 infection in PLWH undergoing treatment. Study design: PLWH were recruited from the Infectious Diseases Outpatient Clinic of Fondazione Policlinico Universitario A.Gemelli IRCCS in Italy and randomly interviewed via a questionnaire during their follow-up visits to determine if they had experienced a SARS-CoV-2 infection between March 2020 and June 2022.For each participant with reported history of SARS-CoV-2 (cases), two PLWH with no declared COVID-19 infection were selected (controls); PLWH had a similar potential exposure time to SARS-CoV-2. A total 220 PLWH were selected: 72 cases and 148 controls. None developed severe Covid-19 disease and only one participant required hospitalization. Results: Overall, 220 PLWH were enrolled: 72 cases and 148 controls. Characteristics of cases and controls were similar, except for the ART regimen used and the last HIV-RNA concentration before the enrollment date. By an adjusted multivariable logistic regression, the estimated odds of SARS-CoV-2 infection was higher in more recent years (2022 versus 2020 aOR 20.74, 95 % CI 5.26–81.8) and in PLWH with last HIV-RNA >50 cp/mL before enrollment date (versus <50 aOR 4.56, 95 % CI 1.01–20.46). A reduced odds was correlated with >3 vaccine doses (versus <3 or not vaccinated aOR 0.08, 95 % CI 0.02–0.24). Conclusion: In this cohort, the odds of SARS-CoV-2 acquisition increased over time, probably due to change in lock-down measures and in SARS-CoV-2 circulating variants.Detectable viral load was associated with increased risk of infection, highlighting the importance of HIV-RNA monitoring during pandemics.